The Social Media Dominance: Ukraine’s Key Strategy in the Information War Against the Russian Invasion - Syahrir Mujib; A. H. S. Reksoprodjo; A.G. Dohamid; David Yacobus (CV. AFDIFAL MAJU BERKAH, 2023)
Russia once again invaded Ukraine in early 2022 by deploying thousands of troops and mobilizing thousands of tanks and other weapons. The attack, which began in February, covered areas along the eastern border of Ukraine. As Ukraine realized that its military power was imbalanced with Russia, it applied information warfare techniques by dominating social media content. This study aims to analyze Ukraine's success in using social media as a tool to combat Russian invasion through social media domination. This research used the descriptive – qualitative method. The data were obtained from the information that were determined which were then analyzed by qualitative method. Netwar theory and propaganda theory are used to analyze this study. The results of this study show that Ukraine has utilized social media to fight against Russia's invasion and has achieved significant success in garnering global support. Social media domination has played a crucial role in Ukraine's efforts to win the support of countries worldwide. The use of humanitarian issues has been heavily emphasized in social media content to condemn Russia's actions. The impact of such content has resulted in a sharp decline in support for Russia. Misinformation spread through social media has also contributed to the decline in support.